2016
DOI: 10.17795/soj-4143
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Injection Injuries to the Hand

Abstract: Background: High-pressure injections into the hand, burden devastating and permanent functional impairments. Many materials including paint, paint thinner, gasoline, oil and grease are reported as the causative agents. These injuries need multiple procedures and reconstructions most of the time and 40% of the injuries may end with amputation of the injured part. Objectives: The aim of this study was to report the treatment outcomes and methods of treatments of patients with high-pressure injection injuries of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Depending on the volume and materials injected, the finger may be distended, swollen, and tender on palpation. If vessels in the involved digit have been thrombosed or compressed, the digit may be pale, anesthetic, or even ischemic [4]. In the case of an air injection injury, associated crepitus and subcutaneous emphysema are possible [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the volume and materials injected, the finger may be distended, swollen, and tender on palpation. If vessels in the involved digit have been thrombosed or compressed, the digit may be pale, anesthetic, or even ischemic [4]. In the case of an air injection injury, associated crepitus and subcutaneous emphysema are possible [7].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it has been reported that this may be due to not only gases but also a variety of liquids such as pressurized paint, grease, diesel fuel, helium, carbon dioxide and nitrous oxide [3]. The injected material has deleterious effects in several ways including a direct toxic effect of the involved chemical, ischemia, high-velocity mechanical impact, secondary infection, a significant rise of pressure in the closed palmar or digital space with consequ-ent compartment syndrome [4]. Despite the nontoxicity of injected air, the importance of acute surgical intervention must be emphasized, as there is a risk of high-pressure soft tissue damage.…”
Section: Introductionmentioning
confidence: 99%